Holistic Characterization of PBF-LB/P Powder Regarding Isothermal Crystallization, Rheology and Optical Properties Under Process Conditions - Marschall, Maximilian; Cholewa, Simon; Kopp, Sebastian-Paul; Drummer, Dietmar; Schmidt, Michael (Additive Manufacturing in Multidisciplinary Cooperation and Production, 2023)
Laser based powder bed fusion of Polymers is an additive manufacturing technology that meets requirements of established manufacturing processes; thus, it is essential to expand the original range of applications from prototype generation to functional components. Semi-crystalline materials, mainly polyamide 12 (PA 12), dominate the market. Prior to solidification, material crystallization takes place during the building phase, yielding changes in material properties including rheology and optical properties. To gain a deep process understanding for reliable part production, a process-adapted evaluation is required to ascertain how long the molten polymer remains amorphous with reduced absorption and viscous dominant behavior, to the point when crystallites are forming. In this contribution, the effect of solidification on optical characteristics during an isothermal process is discussed. The goal of this process adapted characterization method is to reduce feedback circles for powder development, discretize process parameter settings, and obtain a wide range of process relevant material characteristics for PBF-LB/P for the first time in such an integrated manner. This contribution compares temperature-dependent optical properties of a polymer powder layer and melt to rheological behavior of the isothermally solidifying melt pool. To ensure this comparability, both measurement setups are equipped with IR spectroscopy, which allows to analyze the isothermal crystallization progress. A modified double integrating sphere setup with FTIR (Fourier-transform infrared spectroscopy) and a rheometer with ATR (attenuated total reflection) were used. It was found out, that the isothermal crystallization already occurs faster than thought, even within preheating temperatures significantly above crystallization temperature in the upper layers. Thus, curling and thickness variation can appear due to change in absorptance and rheology, and impact the manufacturing quality. This can be a failure criterium for development stage of tailored polymer powders for PBF-LB/P.<br
Keywords: Additive manufacturing; PBF-LB/P; Isothermal crystallization; Rheology; Optical properties